Investigation of high-k yttrium copper titanate thin films as alternative gate dielectrics. (12th September 2016) - Monteduro, Anna Grazia; Ameer, Zoobia; Rizzato, Silvia; Martino, Maurizio; Caricato, Anna Paola; Tasco, Vittorianna; Lekshmi, Indira Chaitanya; Hazarika, Abhijit; Choudhury, Debraj; Sarma, D D; Maruccio, Giuseppe
Abstract: Nearly amorphous high- k yttrium copper titanate thin films deposited by laser ablation were investigated in both metal–oxide–semiconductor (MOS) and metal–insulator–metal (MIM) junctions in order to assess the potentialities of this material as a gate oxide. The trend of dielectric parameters with film deposition shows a wide tunability for the dielectric constant and AC conductivity, with a remarkably high dielectric constant value of up to 95 for the thick films and conductivity as low as 6  ×  10 −10 S cm −1 for the thin films deposited at high oxygen pressure. The AC conductivity analysis points out a decrease in the conductivity, indicating the formation of a blocking interface layer, probably due to partial oxidation of the thin films during cool-down in an oxygen atmosphere. Topography and surface potential characterizations highlight differences in the thin film microstructure as a function of the deposition conditions; these differences seem to affect their electrical properties.